Physiological and Behavioral Manifestations of Children and Teenagers with Down Syndrome During the Dental Appointment: A Comparative Cross-Sectional Study - Aryvelto Miranda Silva; Básia Rabelo Nogueira; Thalles Anthony Chaves Leal; Raimundo Rosendo Prado Júnior; Regina Ferraz Mendes (Association of Support to Oral Health Research (APESB), 2022)
Objective: To measure the heart rate (HR) and the behavior of children and teenagers with Down Syndrome (DS) during the dental appointment. Material and Methods: Two groups (n = 52), of both genders, aged 2-14 years, matched by age group were formed: study group (SG) - individuals with DS and control group (CG) - normotypical school children. The participants were submitted to clinical examination and prophylaxis. An oximeter was used to measure the HR at five moments of the dental consultation: before entering the practice room (T0), when sitting in the dental chair (T1), during  the  clinical examination (T2), during prophylaxis (T3) and immediately after prophylaxis (T4). Behavior, classified according to the Frankl Scale, was observed at T3. Mann Whitney, Kruskal-Wallis, Dunn and Pearson's Chi-square tests were used to analyze and compare variables (significance level at 5%). Results: In SG, a significant difference in HR was observed according to the moment of dental appointment (p<0.001 SG; 0.3385 CG). The highest HR value in SG was observed at T3 (median 110.00; IIQ 96.00-124.00), the only moment significantly different (p<0.001) from HR values for CG. A difference in behavior between groups (p<0.001) was also observed. Conclusion: HR of individuals with DS varied throughout the dental appointment, and they also had a higher prevalence of uncooperative behavior.